Perspectives on evaluation in financial education: Landscape, issues, and studies. Issue 2 (3rd April 2017) - Walstad, William; Urban, Carly; J. Asarta, Carlos; Breitbach, Elizabeth; Bosshardt, William; Heath, Julie; O'Neill, Barbara; Wagner, Jamie; Xiao, Jing Jian
ABSTRACT: This review discusses the heterogeneity in the effectiveness of financial education programs that occurs because of the unique conditions for programs and methods to evaluate them. The authors define six groups served by financial education: children, youth, college students and young adults, working adults, military personnel, and low-income consumers. They then discuss research and evaluation literature for each group with a critical eye on program purpose, content, and evaluation. They also present findings affecting multiple groups on four issues: student loans, homeownership, retirement planning, and financial advising. The accumulated evidence on the effectiveness of financial education is positive, although the results are nuanced and sometimes limited. The authors argue that understanding this broad landscape in studying financial education is critical for future research and evaluation.